Preface to sustainable development problems in the issue - Dzemydienė, Dalė (Technological and Economic Development of Economy, 2008)
“Preface to sustainable development problems in the issue”, Technological and Economic Development of Economy, 14(1), 8–10. First published online: 21 Oct 2010